What to do when a suspected reader an unethical? - Oyola-García, Alfredo (2015)
Most, or almost all, scientific publications follow recommendations of the International Committee of Medical Journal Editors (ICMJE). This committee clearly states that the publication duplicate is a scientific misconduct (1.2), but so can be public defamation, as we have stated in other articles.